"The Invisible Staff": A Qualitative Analysis of Environmental Service Workers' Perceptions of the VA Clostridium difficile Prevention Bundle Using a Human Factors Engineering Approach. Issue 8 (12th December 2021) - Yanke, Eric; Moriarty, Helene; Carayon, Pascale; Safdar, Nasia
Abstract : Objectives: Using a novel human factors engineering approach, the Systems Engineering Initiative for Patient Safety model, we evaluated environmental service workers' (ESWs) perceptions of barriers and facilitators influencing adherence to the nationally mandated Department of Veterans Affairs Clostridium difficile infection (CDI) prevention bundle. Methods: A focus group of ESWs was conducted. Qualitative analysis was performed employing a visual matrix display to identify barrier/facilitator themes related to Department of Veterans Affairs CDI bundle adherence using the Systems Engineering Initiative for Patient Safety work system as a framework. Results: Environmental service workers reported adequate cleaning supplies/equipment and displayed excellent knowledge of CDI hand hygiene requirements. Environmental service workers described current supervisory practices as providing an acceptable amount of time to clean CDI rooms, although other healthcare workers often pressured ESWs to clean rooms more quickly. Environmental service workers reported significant concern for CDI patients' family members as well as suggesting uncertainty regarding the need for family members to follow infection prevention practices. Small and cluttered patient rooms made cleaning tasks more difficult, and ESW cleaning tasks were often interrupted by other healthcare workers. Environmental service workers did not feel comfortable asking physicians for more time to finish cleaning a room nor did ESWs feel comfortable pointing out lapses in physician hand hygiene. Conclusions: Multiple work system components serve as barriers to and facilitators of ESW adherence to the nationally mandated Department of Veterans Affairs CDI bundle. Environmental service workers may represent an underappreciated resource for hospital infection prevention, and further efforts should be made to engage ESWs as members of the health care team.